СИНДРОМ ГИПЕРМОБИЛЬНОСТИ СУСТАВОВ: КЛИНИЧЕСКОЕ ЗНАЧЕНИЕ, ПРОГНОЗ, ВЗАИМОСВЯЗЬ С РИСКОМ ВОЗНИКНОВЕНИЯ ОСТЕОАРТРОЗА - И. А. Викторова; Н. В. Коншу; А. В. Румянцев (Архивъ внутренней медицины)
Hypermobility of joints (HM) and closely associated with him Joint Hypermobility Syndrome (JHS) are very distributed in clinical practice. The family nature of the HM had been found that suggests a genetic nature of the observed phenomena. This syndrome has got a dominant inheritance, mainly through the female line. At the present time we’ve got a sufficient information wich shows HM influences on the occurrence and course of the artrologic diseases. JHS is a factor of risk for the development of early osteoarthritis (OA) which arises in these individuals more often than the other people. Some foreign scientists associate HM and OA, another one suppose that HM provides a protective effect on OA. The issue of the relationship between HM and early OA is discused. Persons with HM, especially if in their families there are patients with OA, it is necessary to recommend preventive measures.